2017
DOI: 10.1155/2017/8785121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV-C Light Exposure and Refrigeration on Phenolic and Antioxidant Profiles of Subtropical Fruits (Litchi, Longan, and Rambutan) in Different Fruit Forms

Abstract: The objectives of this study were to investigate how UV-C irradiation and refrigeration affect shelf-life and antioxidant level of litchi, longan, and rambutan. Three forms (whole, dehulled, and destoned) of fresh fruits were treated by refrigeration and UV-C irradiations. After processing, deterioration rate, phenolics compounds, and antioxidant capacity were quantified. The deterioration rate was recorded as decay index. The results showed that both refrigeration and UV-C exposure extended the shelf-life of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Ca 2+ is an important component of the human body, and is required for vascular contraction, muscle function, nerve transmission, and intracellular signaling (Onstitute of Medicine, 2010). The Na + contents of maca leaves and roots were found to be higher compared to other studies of maca roots as well (Li et al, 2017). Maca leaves and roots are an excellent source of Na + which is an essential mineral for human health required for cellular homeostasis and fluid balance (Farquhar et al, 2015).…”
Section: Chemical and Mineral Composition Of Maca Leaves And Rootsmentioning
confidence: 78%
See 1 more Smart Citation
“…Ca 2+ is an important component of the human body, and is required for vascular contraction, muscle function, nerve transmission, and intracellular signaling (Onstitute of Medicine, 2010). The Na + contents of maca leaves and roots were found to be higher compared to other studies of maca roots as well (Li et al, 2017). Maca leaves and roots are an excellent source of Na + which is an essential mineral for human health required for cellular homeostasis and fluid balance (Farquhar et al, 2015).…”
Section: Chemical and Mineral Composition Of Maca Leaves And Rootsmentioning
confidence: 78%
“…An earlier study showed that dietary intake of K + has a beneficial effect on the coronary heart disease by decreasing blood pressure and maintaining an adequate Na + to K + ratio (Weaver, 2009). The Ca 2+ contents of maca leaves and roots was observed to be higher (6.58 and 2.25 mg/g, respectively) than that reported by other studies of maca roots (Li et al, 2017). Ca 2+ is an important component of the human body, and is required for vascular contraction, muscle function, nerve transmission, and intracellular signaling (Onstitute of Medicine, 2010).…”
Section: Chemical and Mineral Composition Of Maca Leaves And Rootsmentioning
confidence: 92%
“…AAC acts as an antioxidant via scavenging the free radicals created in fruits and thus prevents its degradation, which begins during fruit ripening due to oxidation processes (Khaliq et al., 2015). However, the AA content of the fruit can be affected by a number of factors, such as pre‐ and post‐harvest treatment, harvest time, storage conditions, and oxidative stress (Li et al., 2017; Zhao et al., 2019). The AA content for the fruit gradually decreased in all treated and untreated samples during the storage period ( p < .001) and at the end of 45 day of storage, the AA content reduction in control fruit was more than 26% (6.59 mg/kg FW) (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…The AA content for the fruit gradually decreased in all treated and untreated samples during the storage period ( p < .001) and at the end of 45 day of storage, the AA content reduction in control fruit was more than 26% (6.59 mg/kg FW) (Figure 2b). The postharvest reduction of AA content may have occurred due to thermal degradation and/or chemical oxidation (Li et al., 2017; Zhao et al., 2019). However, this reduction in AA content was significantly ( p < .001) delayed by the application of PPE extract and/or CaSO 4 1% (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…can degrade in light conditions, because the antioxidant ingredients are oxidized when they are exposed to light. 9 Therefore, bright and firm hybrid emulsion I is recommended to be kept under dark condition.…”
Section: Discussionmentioning
confidence: 99%